Post occupancy evaluation for sustainable neighborhood development - Yaman, Rostam; Thadaniti, Suwattana; Suntornvongsagul, Kallaya; Adnan, Hamimah; Ahmad, Noraini (American Scientific Publishers, 2017)
This paper presents the preliminary study of post-occupancy evaluation (POE) model on neighborhood assessment criteria towards sustainable urban development. The aim of the study is to develop a POE model based on sustainable pillar dimensions. The objective is to identify and formulate POE model towards sustainable neighborhood development and to implement the model in assessing & evaluate GBI certified neighborhood towards sustainable urban development for Malaysia. The consensus-based approach is used in this study in order to gather experts’ opinion regarding the proposed POE model for sustainable neighborhood development for the certified GBI neighborhood project. The significant contribution of the research is the POE model for future sustainable neighborhood development for Malaysia and similar development phenomenon in the region of ASEAN nations and country throughout the world.